Russia's Muslims and Electoral Participation: A Comparative Analysis of Regional Patterns - Golosov, Grigorij Vasilʹevič (Islam and Christian-Muslim relations, 2014)
This article examines the impact of Muslim minorities upon the modes of regional electoral politics in Russia. In particular, the interweaving of ethnic and religious aspects proved to be a significant factor in electoral mobilization, determining the levels of electoral activity and success. At the same time, a significant variation observed between the cases of Ulyanovsk and Astrakhan provinces turned out to be impossible to explain without using the characteristics of regional political regimes as explanatory variables. This led to the development of a multifactor model of ethnic Muslim activism. The model starts with the external factors of the political context, and then incorporates factors directly related to ethnicity and religion. The categorization of regional political regimes follows the general distinction between the consensual and conflictual types as developed by Arend Lijphart. The analysis demonstrates that the latter type impairs the conventional political participation and legislative representation of Russia's ethnic Muslims.